(untitled) (Journal of Organizational Psychology, 2023)
Corporate Psychological Responsibility (CPR) is the responsibility of an organization to focus on psychological factors that impact employees to create a competitive advantage for all stakeholders (Sweet, 2020). This manuscript seeks to introduce a framework and model for CPR. A literature review of components that impact employees psychologically in motivational theory and in positive organizational behavior was conducted to identify elements that should be managed to become a psychologically responsible organization. Five pillars of CPR are introduced: health and safety, psychological capital, positive relationships, valued rewards, and fair organizational policies/practices. Organizations that take CPR seriously can create a competitive advantage.